2015
DOI: 10.1021/acsnano.5b00791
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced Size Dependence in Structure and Morphology of Gas-Phase Produced, Partially Oxidized Cobalt Nanoparticles under Catalytic Reaction Conditions

Abstract: It is generally accepted that optimal particle sizes are key for efficient nanocatalysis. Much less attention is paid to the role of morphology and atomic arrangement during catalytic reactions. Here, we unravel the structural, stoichiometric, and morphological evolution of gas-phase produced and partially oxidized cobalt nanoparticles in a broad size range. Particles with diameters between 1.4 and 22 nm generated in cluster sources are size selected and deposited on amorphous alumina (Al2O3) and ultrananocrys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 80 publications
1
18
0
1
Order By: Relevance
“…The method has acquired particular popularity as is evidenced by an increasing number of papers that have been published in recent years. Single-metal, [4][5][6][7][8][9][10][11][12][13][14][15] alloyed [16][17][18][19][20][21][22][23][24][25][26] and heterostructured NPs [27][28][29][30][31][32][33][34][35][36][37][38][39][40] have been successfully synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…The method has acquired particular popularity as is evidenced by an increasing number of papers that have been published in recent years. Single-metal, [4][5][6][7][8][9][10][11][12][13][14][15] alloyed [16][17][18][19][20][21][22][23][24][25][26] and heterostructured NPs [27][28][29][30][31][32][33][34][35][36][37][38][39][40] have been successfully synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…[59] Such "atom-by-atom" insight into the catalytic activity and selectivity of supported clusters is only possible through the preparation of welldefined samples by the soft landing of mass-selected ions. [61] Interestingly,s mall and intermediate-size clusters retained their morphology,w hile larger particles transformed into hollow spheres as aresult of the nanoscale Kirkendall effect. Forexample,characterization of Pd n clusters soft landed onto TiO 2 supports revealed that deactivation proceeds through an alloy-like,s trong metal-support interaction that chemically modifies the clusters through electronic interactions with the support.…”
Section: Catalytic Particles-from Isolated Ions To Particle Assembliesmentioning
confidence: 98%
“…[60] Thes tructural evolution of size-selected (1.4-22 nm diameter) cobalt nanoparticles during the oxidative dehydrogenation of cyclohexane was also explored. [61] Interestingly,s mall and intermediate-size clusters retained their morphology,w hile larger particles transformed into hollow spheres as aresult of the nanoscale Kirkendall effect. Larger bimetallic nanoparticles containing Co and Pt were prepared on alumina supports and characterized using in situ X-ray scattering and absorption techniques to examine the evolution of their size,shape,and oxidation state under the reaction conditions.…”
Section: Catalytic Particles-from Isolated Ions To Particle Assembliesmentioning
confidence: 98%
“…[60] Untersucht wurden auch Strukturänderungen von grçßenselektierten Co-Nanopartikeln (1.4-22 nm Durchmesser) während der oxidativen Dehydrierung von Cyclohexan. [61] Interessanterweise behielten kleinere und mittlere Cluster ihre Morphologie bei, während sich große Partikel in Hohlkugeln umwandelten, was auf den Kirkendall-Effekt zurückzuführen ist. Grçßere Dimetallnanopartikel aus Co und Pt wurden auf Aluminiumoxid aufgebracht und mit In-situ-Rçntgenstreuungu nd -Absorptionstechniken untersucht, um ¾nderungen von Grçße,F orm und Oxidationszustand unter den Reaktionsbedingungen zu verstehen.…”
Section: Angewandte Chemieunclassified